Microwave imaging - Pastorino, Matteo (Hoboken, N.J. : John Wiley, 2010)
Microwave imaging--a technique used in sensing a given scene by means of interrogating microwaves--has recently proven its usefulness in providing excellent diagnostic capabilities in several areas, including civil and industrial engineering, nondestructive testing and evaluation, geophysical prospecting, and biomedical engineering. Microwave Imaging offers comprehensive descriptions of the most important techniques so far proposed for short-range microwave imaging--including reconstruction procedures and imaging systems and apparatus--enabling the reader to use microwaves for diagnostic purposes in a wide range of applications. Microwave Imaging is a practical resource for engineers, scientists, researchers, and professors in the fields of civil and industrial engineering, nondestructive testing and evaluation, geophysical prospecting, and biomedical engineering.--Publisher's description.
Includes bibliographical references and index.
Keywords: Microwave imaging -- Industrial applications; Nondestructive testing; Radiography, Industrial